IMPLEMENTASI PENGGUNAAN METODE DONGENG DALAM EDUKASI PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK DI SDN TANJUNG ILIR - Diva Nurzahwa, Felani; Pertiwi, Fitri; Fatimah, Nining (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the increasing number of cases of sexual violence against children and the importance of providing preventive education that is appropriate to the developmental characteristics of elementary school children. This study aims to analyze the implementation of the storytelling method in education on preventing sexual violence against children at Tanjung Ilir Elementary School. The study used a qualitative approach with a descriptive approach. The subjects were 10 students from Tanjung Ilir Elementary School who participated in educational activities and mentoring by the Indonesian Brother and Sister Foundation. Data collection techniques were conducted through observation and interviews. The results showed that the storytelling method was able to create an interactive and enjoyable learning atmosphere, making it easier for students to understand the material presented. The educational activities were carried out through several stages: an introduction, telling the story